Puerto Rico’s Domestic Violence Prevention and Intervention Law and the United States’ Violence Against Women Act of 1994: The Limitations of Legislative Responses - Rivera, Jenny (Columbia Journal of Gender and Law, 1995)
Annually, three to four million women are targets of violence by their intimate partners or spouses. The women who survive this violence endure physical, verbal, emotional, and psychological abuse that threatens their health, and often their lives. The daily incidences of violence include severe physical abuse. Even more alarming is the number of women who die at the hands of their intimate partners: violence against women by spouses or intimate male companions accounts for thirty percent of all homicides of women. In 1990 alone, over 800 women were killed by their husbands and another 400 were killed by their male companions. There is no avoiding or denying the prevalence and nondiscriminative nature of this violence, for it “cuts across all racial, ethnic, religious, educational and socio-economic lines.” Violence against women by their former and current male partners is commonly referred to as domestic violence, partially because it involves the personal dynamics of intimate relationships. The effects of this violence, nevertheless, extend beyond the confines of the domestic sphere. First, because family, neighbors, and law enforcement officials may have direct or direct knowledge of this violence, it cannot be summarily categorized as strictly private. Second, because of its detrimental impact on women’s lives and on the social and human services which bind society, it has larger social and political implications. Indeed, in 1991, the United States Surgeon General announced that domestic violence is the second leading cause of injury to women. Although the cost of the violence in dollars and cents is of secondary importance, and pales in comparison to the numerous lives lost or shattered as a direct consequence of this violence, it is, nonetheless, notable. In economic terms, this violence has had devastating cost implications for public and private medical and legal services and has drained already scarce resources.